Design and Synthesis of Novel Bis-Imidazolyl Phenyl Butadiyne Derivatives as HCV NS5A Inhibitors - Jehad Hamdy; Nouran Emadeldin; Mostafa M. Hamed; Efseveia Frakolaki; Sotirios Katsamakas; Niki Vassilaki; Grigoris Zoidis; Anna K. H. Hirsch; Mohammad Abdel-Halim; Ashraf H. Abadi (MDPI AG, 2022)
In today's global plan to completely eradicate hepatitis C virus (HCV), the essential list of medications used for HCV treatment are direct-acting antivirals (DAAs), as interferon-sparing regimens have become the standard-of-care (SOC) treatment. HCV nonstructural protein 5A (NS5A) inhibitors are a very common component of these regimens. Food and Drug Administration (FDA)-approved NS5A inhibitors, although very potent, do not have the same potency against all eight genotypes of HCV. Therefore, this study aims to synthesize NS5A inhibitor analogues with high potency pan-genotypic activity and high metabolic stability. Starting from an NS5A inhibitor scaffold previously identified by our research group, we made several modifications. Two series of compounds were created to test the effect of changing the length and spatial conformation (para-para vs. meta-meta-positioned bis-imidazole-proline-carbamate), replacing amide groups in the linker with imidazole groups, as well as different end-cap compositions and sizes. The frontrunner inhibits genotype 1b (Con1) replicon, with an EC50 value in the picomolar range, and showed high genotypic coverage with nanomolar range EC50 values against four more genotypes. This together with its high metabolic stability (t½ > 120 min) makes it a potential preclinical candidate.